1989
DOI: 10.2739/kurumemedj.36.81
|View full text |Cite
|
Sign up to set email alerts
|

Gastric operations in patients with hepatic cirrhosis following endoscopic sclerotherapy.

Abstract: Three patients with hepatic cirrhosis who had undergone gastric operations following endoscopic sclerotherapy were retrospectively reviewed. One patient had undergone total gastrectomy for gastric cancer and two had Hassab and Tanner operations for gastric and esophageal varices. All patients were recovering with no complications related to the operations and were free of disease for 2 years, postoperatively.When esophageal varices are found in combination with an upper gastric cancer that requires total gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this situation, preoperative sclerotherapy for varices is contraindicated because of esophageal damage caused by the sclerosing agents (Takeda et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, preoperative sclerotherapy for varices is contraindicated because of esophageal damage caused by the sclerosing agents (Takeda et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“… 5–7 were the first to report gastroesophageal devascularization and splenectomy for the treatment of esophageal varices, although it did not gain wide acceptance at that time because of the high recurrence rate. However, in light of the recent progress in endoscopic treatments for esophageal varices, EGDS after endoscopic treatments has undergone a resurged interest 60–62 . EGDS has three effeccts in treating varices; first is a decreased inflow by splenectomy, second is devascularization of the risky peri‐gastroesophageal collaterals, and the third is no huge portosystemic shunt formation 5–7 .…”
Section: Indication Of Splenectomy In Hepatic Disordersmentioning
confidence: 99%
“…However, in light of the recent progress in endoscopic treatments for esophageal varices, EGDS after endoscopic treatments has undergone a resurged interest. [60][61][62] EGDS has three effeccts in treating varices; first is a decreased inflow by splenectomy, second is devascularization of the risky peri-gastroesophageal collaterals, and the third is no huge portosystemic shunt formation. [5][6][7] Hashizume et al 62 reported that recurrence rate after laparoscopic EGDS was 0% with blood loss of 500 mL during surgery.…”
Section: Splenectomy For Esophagogastric Varicesmentioning
confidence: 99%
“…Postoperative care included water and sodium restriction, infusions of albumin and fresh-frozen plasma, diuretic and antibiotic therapy. (Takeda et al 1989).…”
Section: Discussionmentioning
confidence: 99%